FUNGSI DASAR MANAJEMEN DALAM KONTEKS MODERN: ANALISIS PERENCANAAN, PENGORGANISASIAN, DAN PENGENDALIAN - Siti Mulasih; Roviyanti Darozah; Hadi Sutrisno; Hajarudin; Farhat Abbas; Alifi Restu Putera (POLITEKNIK LP3I JAKARTA, 2024)
This research aims to explore the implementation of the basic management functions of planning, organizing, directing, and controlling in the context of modern organizations influenced by technological advances and sustainability principles. The method used is a literature-based and case study approach to analyze the role of digital technologies, such as big data and automation, in supporting data-driven strategic planning, organizing cross-disciplinary teams, and controlling technology-based performance. The results show that transformational leadership is highly relevant in hybrid and remote work environments, which can increase employee motivation and engagement. In addition, the application of sustainability principles in management has a positive impact on organizational reputation and performance in the long term. This research confirms that the adaptation of management functions to technology and sustainability is critical for organizational success in this digital age.